2022
DOI: 10.3390/ph15030341
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone Synthetic Analogue Ameliorates Streptozotocin-Induced Diabetes Mellitus through Modulation of ACE 2/Angiotensin 1–7 via PI3K/AKT/mTOR Signaling Pathway

Abstract: The renin angiotensin aldosterone system has a localized key regulatory action, especially in liver and body circulation. Furthermore, it accomplishes a significant role in the downregulation of the PI3K/AKT/mTOR signaling pathway that is involved in type II diabetes mellitus pathogenesis. The current study aimed to evaluate the effect of a synthetic pioglitazone analogue (benzenesulfonamide derivative) compared to the standard pioglitazone hypoglycemic drug on enhancing liver insulin sensitivity via ACE 2/Ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Previous clinical studies have shown that siRNA-CYP4A14 can inhibit the proliferation and fibrosis of mesangial cells, which can be considered a therapeutic target for DN. Ahmed et al (2022) found that the reninangiotensin-aldosterone system has a key regulatory role locally, particularly in the liver and body circulation, and is also involved in the pathogenesis of type II diabetes by downregulating the phosphatidylinositol-3-kinase/protein kinase B/mammalian target of rapamycin (PI3K/AKT/ mTOR) signaling pathway. The hypoglycemic effect of benzenesulfonamide derivatives is to enhance the sensitivity of the liver to regulate blood glucose levels through the PI3K/AKT/mTOR pathway (Ahmed et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous clinical studies have shown that siRNA-CYP4A14 can inhibit the proliferation and fibrosis of mesangial cells, which can be considered a therapeutic target for DN. Ahmed et al (2022) found that the reninangiotensin-aldosterone system has a key regulatory role locally, particularly in the liver and body circulation, and is also involved in the pathogenesis of type II diabetes by downregulating the phosphatidylinositol-3-kinase/protein kinase B/mammalian target of rapamycin (PI3K/AKT/ mTOR) signaling pathway. The hypoglycemic effect of benzenesulfonamide derivatives is to enhance the sensitivity of the liver to regulate blood glucose levels through the PI3K/AKT/mTOR pathway (Ahmed et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Ahmed et al (2022) found that the reninangiotensin-aldosterone system has a key regulatory role locally, particularly in the liver and body circulation, and is also involved in the pathogenesis of type II diabetes by downregulating the phosphatidylinositol-3-kinase/protein kinase B/mammalian target of rapamycin (PI3K/AKT/ mTOR) signaling pathway. The hypoglycemic effect of benzenesulfonamide derivatives is to enhance the sensitivity of the liver to regulate blood glucose levels through the PI3K/AKT/mTOR pathway (Ahmed et al, 2022). Taken together, these studies indicate that the five genes we identified may provide new therapeutic targets for the treatment of DN.…”
Section: Discussionmentioning
confidence: 99%
“…STZ (T2D) positive control group: receiving intraperitoneal STZ injection (45 mg/kg) [ 120 ] after being subjected to three consecutive weeks of HFD feeding [ 77 ];…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, PPARƳ enhances nitric oxide (NO) production in the endothelium and retracts ET-1 expression, promoting endothelial relaxation [ 75 , 76 ]. Ahmet et al [ 77 ] reported that pioglitazone analogue significantly regulates Streptozotocin-Induced T2D through stimulating local angiotensin-converting enzyme 2/angiotensin 1-7 axis with the aid of PI3K/AKT/mTOR Signaling pathway in the hepatic tissues, thereby regulating glycogen deposition and enhancing lipolysis. However, Molavi et al [ 78 ] found that PPARƳ ligand rosiglitazone protects against myocardial ischemia/reperfusion injury via an effect on AT2 receptor upregulation and p42/44 MAPK inhibition.…”
Section: Introductionmentioning
confidence: 99%